Dinamika Hukum Konstitusi dan Tantangan Praktik Demokrasi di Indonesia: Studi Kritis terhadap Oligarki Politik dan Reformasi Sistem Pemilu - Denis Irwin; Muhammad Dwi Erwiansyah; Dayyah Khairullah; Ade Fartini (Cattleya Darmaya Fortuna, 2025)
The trajectory of Indonesia’s constitutional law following the 1998 reform era demonstrates a profound legal evolution driven by amendments to the 1945 Constitution, which were intended to reinforce democratic governance, the supremacy of law, and state transparency. Yet, the implementation of substantial constitutional democracy continues to face numerous obstacles. These include the persistence of political oligarchies, the partiality of electoral institutions, weak inter-institutional oversight, the prevalence of money politics, and the high presidential threshold that restricts equal political competition. This study seeks to examine the current dynamics of Indonesia’s constitutional framework, identify the underlying issues within democratic practice, and formulate an ideal model for reconstructing constitutional law to promote justice and strengthen the rule of law. Employing a normative-juridical approach complemented by limited empirical insights, the research analyzes relevant legal instruments and compares them with constitutional mechanisms applied in other democratic nations. The study concludes that advancing Indonesia’s constitutional order requires reforms in the electoral system, enhancement of independent election management bodies, and stronger law-enforcement mechanisms. In response, the paper recommends a reconstruction of constitutional law that is adaptive to modern political realities by emphasizing constitutional supremacy, institutional transparency, and accountability in governance. The contribution of this research lies in its integrative critique of post-reform constitutional weaknesses and in offering strategic directions for achieving a more substantive and equitable democratic order in Indonesia.